Two-year follow-up of unilateral biportal endoscopy assisted extraforaminal lumbar interbody fusion: how to perform indirect decompression and fusion under endoscopy: a retrospective study in Japan - Takaki Yoshimizu; Sanshiro Saito; Teruaki Miyake; Tetsutaro Mizuno; Ushio Nosaka; Keisuke Ishii; Mizuki Watanabe; Kanji Sasaki (Asian Spine Journal)
Study Design Retrospective study. Purpose To compare the clinical and radiographic outcomes of unilateral biportal endoscopy-assisted extraforaminal lumbar interbody fusion (BE-ELIF) and oblique lateral interbody fusion (OLIF). Overview of Literature OLIF is widely recognized for its strong realignment capability, achieved through placing a large interbody cage, and its favorable clinical outcomes with indirect decompression. ELIF, similar to OLIF, does not entail exposure of the spinal canal. At our hospital, BE-ELIF involves removing the superior articular processes on both sides, inserting two expandable cages, and performing indirect canal decompression. BE-ELIF is a lumbar interbody fusion technique that provides indirect decompression similar to OLIF. However, no studies have compared the efficacy of ELIF performed under unilateral biportal endoscopy with that of OLIF. Methods Forty-nine adults who underwent single-level L4/5 interbody fusion for degenerative spondylolisthesis were divided into BE-ELIF (n=27) and OLIF (n=22) groups based on the surgical approach used. Clinical outcomes were assessed using the Visual Analog Scale and the Japanese Orthopedic Association Back Pain Evaluation Questionnaire (JOABPEQ). Radiographic parameters, including distance of spondylolisthesis, disc height, segmental lordosis, lumbar lordosis, pelvic tilt, and sagittal vertical axis, were evaluated preoperatively and at final follow-up. Results OLIF provided significantly better relief of pain in lower limbs and buttocks at 1-year follow-up. No significant between-group differences were observed in JOABPEQ domains. BE-ELIF resulted in greater improvements in spondylolisthesis distance and disc height, while other parameters did not differ significantly between the two groups. Conclusions For L4/5 degenerative spondylolisthesis, BE-ELIF demonstrated superior spondylolisthesis reduction and disc height improvement than OLIF. Although BE-ELIF was associated with some inferior clinical outcomes, it provided satisfactory results, effective realignment, and a low complication risk.